Effect of levodopa on healthy volunteers' facial emotion perception: an FMRI study - Delaveau, Pauline; Salgado-Pineda, Pilar; Wicker, Bruno; Micallef-Roll, Joëlle; Blin, Olivier (Clinical neuropharmacology, 2005)
A link between the brain dopaminergic (DA) system and emotional processing seems to be supported by the DA nature of neural systems surrounding emotional recognition, the occurrence of emotional deficits in medical disorders involving a DA dysfunction, and the effect of DA agonists or antagonists on emotional processing. The authors tested the influence of levodopa administration on emotional processing in a functional MRI (fMRI) study of 10 elderly volunteers. A placebo-controlled, cross-over experimental design was used. Subjects received either levodopa (100 mg) or placebo in 2 fMRI sessions. Performance was evaluated with a passive facial emotion perception test. During the placebo situation, the region-of-interest (ROI) analysis showed that emotional processing activated the bilateral amygdala. In levodopa volunteers, this activation was missing. The statistical comparison between the 2 situations (emotional vs control condition) revealed a highly significant reduction in activation of the bilateral amygdala for the levodopa fMRI session (P corrected <0.0001 in the left and P = 0.002 in the right amygdala). These results suggest that administration of levodopa to healthy volunteers directly or indirectly impairs the amygdalar activation during the emotional perception task. The authors hypothesized that amygdala activation may conform to an inverted U-shaped function in relation to changing dopamine levels.